2019
DOI: 10.1007/s10509-019-3590-4
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological determination to the values of the pre-factors in the logarithmic corrected entropy-area relation

Abstract: In this paper, we continue investigating the possible values of the pre-factors α and β in the logarithmic corrected entropy-area relation based on cosmological stability arguments. In a previous study, we have investigated the stability of the entropy-corrected cosmology using an empirical hyperbolic form of the scale factor. We found that the zero values of the two pre-factors are necessary to obtain a stable flat universe with a deceleration-acceleration transition and no causality violation. The necessity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…While the flat universe is supported by many observational and theoretical works [59][60][61][62][63], Some recent observations of CMB anisotropies also suggest a closed universe [64][65][66][67]. The current theoretical work supports the closed universe where we found that the existence of a stable bouncing cosmology in f (R, T ) gravity is related to the positive curvature.…”
Section: Introductionsupporting
confidence: 79%
“…While the flat universe is supported by many observational and theoretical works [59][60][61][62][63], Some recent observations of CMB anisotropies also suggest a closed universe [64][65][66][67]. The current theoretical work supports the closed universe where we found that the existence of a stable bouncing cosmology in f (R, T ) gravity is related to the positive curvature.…”
Section: Introductionsupporting
confidence: 79%
“…The cosmology has been investigated using a given scale factor a(t) deduced from the desired cosmic behavior which is the opposite of the conventional viewpoint. Such ad hoc approach for cosmic scale factor and cosmological scalar fields has been widely used in the literature by many authors in different theories [2,29,30,31,32,33,34,35,36,37,38,39]. We will make use of both the hyperbolic and the hybrid scale factors given respectively as:…”
Section: F (R T ) Modified Gravitymentioning
confidence: 99%
“…The evolution of these two parameters should lead to a cosmic deceleration-acceleration transit along with a flat ΛCDM model at late-time. This ad hoc approach for the scale factor and scalar fields has been used extensively in the literature to probe the cosmology of several gravity theories [24,25,26,27,28,29,30,31,32].…”
Section: Cosmological Solutions and The Ad Hoc Approachmentioning
confidence: 99%